Evolutionary context for the association of γ-globin, serum uric acid, and hypertension in African Americans. Issue 1 (December 2015) - Shriner, Daniel; Kumkhaek, Chutima; Doumatey, Ayo; Chen, Guanjie; Bentley, Amy; Charles, Bashira; Zhou, Jie; Adeyemo, Adebowale; Rodgers, Griffin; Rotimi, Charles
Abstract Background Hyperuricemia and associated cardio-metabolic disorders are more prevalent in African Americans than in European Americans. We used genome-wide admixture mapping and association testing to identify loci with ancestry effects on serum uric acid levels. Methods We analyzed 1, 976 African Americans from Washington, D.C, including 1, 322 individuals from 328 pedigrees and 654 unrelated individuals, enrolled in the Howard University Family Study. We performed admixture mapping and genome-wide association testing using ~800 k autosomal single-nucleotide polymorphisms (SNPs). We performed fine mapping by dense genotyping. We assessed functionality by a combination of bioinformatic annotation, reporter gene assays, and gel shift experiments. We also analyzed 12, 641 individuals enrolled in the National Health and Nutrition Examination Survey. Results We detected a genome-wide significant locus on chromosome 11p15.4 at which serum uric acid levels increased with increasing African ancestry, independent of kidney function. Fine-mapping identified two independent signals in the β-globin locus. The ancestral allele at SNP rs2855126, located upstream of the hemoglobin, gamma A geneHBG1, was associated with increased serum uric acid levels and higher expression of a reporter gene relative to the derived allele. Hyperuricemia was associated with increased risk of hypertension in 3, 767 African Americans (Odds Ratio = 2.48, p  = 2.71 × 10− 19 ). Conclusions Given that increased expression of γ-globin leads to increased levels of fetal hemoglobin which confers protection against malaria, we hypothesize that evolution in Africa of protection against malaria may have occurred at the cost of increased serum uric acid levels, contributing to the high rates of hyperuricemia and associated cardio-metabolic disorders observed in African Americans.